-3(x-5)=-2(x-8)

Simple and best practice solution for -3(x-5)=-2(x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-5)=-2(x-8) equation:



-3(x-5)=-2(x-8)
We move all terms to the left:
-3(x-5)-(-2(x-8))=0
We multiply parentheses
-3x-(-2(x-8))+15=0
We calculate terms in parentheses: -(-2(x-8)), so:
-2(x-8)
We multiply parentheses
-2x+16
Back to the equation:
-(-2x+16)
We get rid of parentheses
-3x+2x-16+15=0
We add all the numbers together, and all the variables
-1x-1=0
We move all terms containing x to the left, all other terms to the right
-x=1
x=1/-1
x=-1

See similar equations:

| -1/2x+8=-3/4X+9 | | 7r^2-1=-4r | | -5(3x-19)=2(x-2)-3 | | x+14+x+9+5x-10=180 | | 13(z+4)-6=23(5-z) | | -2h-8=-4h+16 | | 180-120+2x=180 | | 3(c−13)=−36 | | F=9x6 | | 3(q-88)=-12 | | 8x+14=4x-6 | | 4m-16=8 | | 180-120+2x=0 | | -4=f-9 | | 180-120+3x=0 | | 2x-(9-6x)=6x | | 5+3c=41 | | 6^-7t=0.60 | | 9k+5=3k+35 | | 3/c=c/27 | | 99=9(k+3) | | 1/2(x-40)=55+8x | | 5x+10°=70° | | 4x-43=57 | | 3n^2-2=-9 | | n2−2n−15=0 | | F(a+4)=-2a^2-a | | 3n+13=52 | | 81=9y+9 | | 3g-36=16+16 | | 5w+15=7w-7 | | 18+4x=3(-x+6)-56 |

Equations solver categories